Lifeboat ethics, risk, and therapeutic opportunity: an appeal for equitable psychedelic therapy access in the “high-risk” addiction patient - Black, Taylor (Frontiers in Psychiatry, 2023)
Psychedelic-assisted treatment (PAT) for mental health is in renaissance. Psilocybin and MDMA stand near FDA approval, and US cities and states are decriminalizing or regulating the non-clinical use of psilocybin. However, neither FDA indications nor a regulated use model sufficiently address the complex needs and opportunities for an improved treatment of addiction. When paired with disability and social dispossession, addiction increasingly burdens informal care networks, public safety, and particularly healthcare systems. Stigma and mistreatment alienate people from opportunities for care and multiply the costs of providing care. This dynamic worsens socially determined resource limitations, enforcing stark ethical choices and perpetuating socioeconomic inequities, isolation, mental illness, medical illness, overdose, suicide, and violence. In order for psychedelic treatments to achieve their greatest utility to population health, we must intentionally develop regulatory, clinical, and payment systems supporting clinical research, rigorous safety monitoring, and implementation to address these immense needs and reduce the barriers to engagement for those who now bear the costs, including those who work at the front lines of addiction care. To achieve full fruition, I advocate for a collaborative approach, built from within networks of mutual social support but linked and accountable to public institutions charged with the equitable dissemination of these therapies for the greatest social and health equities. Rather than relegating PAT to the needs of the commercially insured or wellness markets, this is the moment to learn from ancient traditions of ritualized sacramental use, organized around faith in our mutual dependency and accountability, and to capture an opportunity to improve population health and equity. To miss this opportunity is to accept the status quo in the midst of a growing emergency, for lack of moral vision and intention to change our habits.